Human–rat integrated microRNAs profiling identified a new neonatal cerebral hypoxic–ischemic pathway melatonin‐sensitive. Issue 2 (22nd July 2022) - Weiss, Michael D.; Carloni, Silvia; Vanzolini, Tania; Coppari, Sofia; Balduini, Walter; Buonocore, Giuseppe; Longini, Mariangela; Perrone, Serafina; Sura, Livia; Mohammadi, Atefeh; Rocchi, Marco Bruno Luigi; Negrini, Massimo; et al.
Abstract: Neonatal encephalopathy (NE) is a pathological condition affecting long‐term neurodevelopmental outcomes. Hypothermia is the only therapeutic option, but does not always improve outcomes; hence, researchers continue to hunt for pharmaceutical compounds. Melatonin treatment has benefitted neonates with hypoxic–ischemic (HI) brain injury. However, unlike animal models that enable the study of the brain and the pathophysiologic cascade, only blood is available from human subjects. Therefore, due to the unavailability of neonatal brain tissue, assumptions about the pathophysiology in pathways and cascades are made in human subjects with NE. We analyzed animal and human specimens to improve our understanding of the pathophysiology in human neonates. A neonate with NE who underwent hypothermia and enrolled in a melatonin pharmacokinetic study was compared to HI rats treated/untreated with melatonin. MicroRNA (miRNA) analyses provided profiles of the neonate's plasma, rat plasma, and rat brain cortexes. We compared these profiles through a bioinformatics tool, identifying Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways common to HI brain injury and melatonin treatment. After evaluating the resulting pathways and the literature, to validate the method, the key proteins expressed in HI brain injury were investigated using cerebral cortexes. The upregulated miRNAs in human neonate and rat plasma helped identify two KEGG pathways, glioma and long‐term potentiation, common to HI injury and melatonin treatment. A unified neonatal cerebral melatonin‐sensitive HI pathway was designed and validated by assessing the expression of protein kinase Cα (PKCα), phospho (p)‐Akt, and p‐ERK proteins in rat brain cortexes. PKCα increased in HI‐injured rats and further increased with melatonin. p‐Akt and p‐ERK returned phosphorylated to their basal level with melatonin treatment after HI injury. The bioinformatics analyses validated by key protein expression identified pathways common to HI brain injury and melatonin treatment. This approach helped complete pathways in neonates with NE by integrating information from animal models of HI brain injury.